Triboelectric energy harvesting in harsh conditions: Temperature and pressure effects in methane and crude oil environments. (June 2020) - Rodrigues, C.; Kumar, M.; Proenca, M.P.; Gutierrez, J.; Melo, R.; Pereira, A.; Ventura, J.
Abstract: Environmental and safety sensing is becoming increasingly important in the oil and gas industry. However, present solutions to feed theses sensors are expensive and dangerous and there is so far no technology able to generate electrical energy in the operational conditions of oil and gas extraction wells. Here, we show that triboelectric nanogenerators (TENGs) can withstand and harvest energy in harsh conditions. TENGs are a new technology able to efficiently harvest mechanical energy from the environment. By conducting thorough experiments in methane and crude oil over large ranges of pressures and temperatures, we were able to extend the operation realm of TENGs. By independently varying temperature (25–80 ∘ C) and pressure (28–119 bar) in methane, we demonstrate that temperature is the most critical parameter for TENGs operating in harsh environments. Furthermore, energy harvesting experiments performed in crude oil reveal a decrease of the electric outputs with increasing crude temperature and pressure. Nevertheless, the assembled device continued to generate electrical energy up to pressures of 830 bar and temperatures of 120 ∘ C. This study clearly demonstrates the suitability of triboelectric devices to harvest energy in harsh environments opening a wide new range of possible applications. Graphical abstract: Image 1 Highlights: A TENG was developed to generate electrical energy in oil & gas environments in harsh conditions. The electric outputs decrease with increasing crude temperature and pressure. Temperature is the most critical parameter affecting TENG performance. The assembled TENG was able to charge a capacitor up to 830 bar and 120 °C in crude oil.